2021
DOI: 10.1016/j.heliyon.2021.e06008
|View full text |Cite
|
Sign up to set email alerts
|

Kidney diseases and COVID-19 infection: causes and effect, supportive therapeutics and nutritional perspectives

Abstract: Recently, the novel coronavirus disease 2019 , has attracted the attention of scientists where it has a high mortality rate among older adults and individuals suffering from chronic diseases, such as chronic kidney diseases (CKD). It is important to elucidate molecular mechanisms by which COVID-19 affects the kidneys and accordingly develop proper nutritional and pharmacological strategies. Although numerous studies have recently recommended several approaches for the management of COVID-19 in CKD, its impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 171 publications
(205 reference statements)
1
28
0
4
Order By: Relevance
“…Patients with CKD are highly susceptible to COVID-19 and are at an increased risk of progression to a severe or critical form of the disease because of impaired immunity; additionally, they are at enhanced risk of SARS-CoV-2 infection due to frequent hospital attendance [ 2 , 13 , 14 , 15 , 16 , 17 , 18 ]. The prevalence of CKD in patients with COVID-19 has been reported in a wide range of approximately 1–47%; however, it is suggested that the lowest values result from underestimation [ 16 , 19 , 20 , 21 ]. Among patients with COVID-19 hospitalized in 30 Polish centers included in the current analysis, nearly 20% were diagnosed with CKD, of which 18% presented severe renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD are highly susceptible to COVID-19 and are at an increased risk of progression to a severe or critical form of the disease because of impaired immunity; additionally, they are at enhanced risk of SARS-CoV-2 infection due to frequent hospital attendance [ 2 , 13 , 14 , 15 , 16 , 17 , 18 ]. The prevalence of CKD in patients with COVID-19 has been reported in a wide range of approximately 1–47%; however, it is suggested that the lowest values result from underestimation [ 16 , 19 , 20 , 21 ]. Among patients with COVID-19 hospitalized in 30 Polish centers included in the current analysis, nearly 20% were diagnosed with CKD, of which 18% presented severe renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D, which is also important for renal transplantation patients, is also prominent in the COVID-19 pandemic due to its anti-inflammatory effects[ 6 , 30 ]. In response to COVID-19 infection, vitamin D can prevent disease progression through the production of antimicrobial peptides in the respiratory epithelium and help reduce inflammatory response[ 31 ]. Vitamin D deficiency has been reported to increase the rate of hospitalization and mortality due to COVID-19[ 32 ].…”
Section: Nutritional Therapy After Renal Transplantationmentioning
confidence: 99%
“…Vitamin C contributes to immunity by supporting both the innate and adaptive immune system, modulating inflammatory mediators, and influencing epithelial barriers. It has important benefits such as preventing common cold and upper respiratory tract infections, reducing the duration and severity of the disease and supporting respiratory defense mechanisms[ 31 ]. In addition, it is thought that vitamin C may have a positive effect against COVID-19, as many upper respiratory tract infections are caused by endemic coronaviruses[ 33 ].…”
Section: Nutritional Therapy After Renal Transplantationmentioning
confidence: 99%
See 2 more Smart Citations